Strategi Penurunan Prevalensi Stunting di Kampung KB Desa Palipi Soreang Kabupaten Majene: Studi Analisis Kebijakan dan Intervensi Komunitas Berbasis Hukum Keluarga: Strategies for Reducing the Prevalence of Stunting in Kampung KB, Palipi Soreang Village, Majene Regency: A Study of Policy Analysis and Community-Based Interventions Based on Family Law - Rahman, Abdul; Mas’ud, Bulqia; Janur, Nur Akifah; Bunawan I Daimun (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
Stunting is a chronic nutritional problem that has a multidimensional impact on the quality of human resources. This study aims to identify strategies to reduce stunting in the KB Village of Palipi Soreang Village, Majene Regency, as a priority area in West Sulawesi. Using a qualitative approach and case study method, data were collected through in-depth interviews, FGDs, participatory observation and documentation. The results showed the significant success of Palipi Soreang Village in reducing the prevalence of stunting through strengthening village regulations, activating Posyandu and the Family Assistance Team, and involving village youth. These strategies are effective when combined with nutrition education, early marriage supervision, and inter-sectoral synergy. This study recommends the integration of stunting interventions into village development policies based on the Islamic family law approach, as well as cadre empowerment and merit-based incentives.